Graduated compression stockings and delayed onset muscle soreness - Perrey, S.; Bringard, A.; Racinais, S.; Puchaux, K.; Belluye, N. (The Engineering of sport 7, Volume 1, 2008)
Delayed onset muscle soreness (DOMS) is a common experience following unaccustomed eccentric exercise. DOMS and associated force deficits may limit optimal performance in subsequent days. The cause of DOMS remains poorly understood, thus there is no effective treatment. Graduated compression stockings (GCS) are a commonly used Intervention believed to diminish DOMS. The purpose of this study was to determine if GCS after eccentric walking exercise minimizes DOMS and associated deficits (e.g. muscle force capa-city). Eight healthy subjects {age 26±4 yrs, height 175±8 cm, weight 70±5 kg) volunteered to perform a single bout of backward downhill walking exercise (duration 30 min, velocity 1 m.s-1, negative grade -25%, load 12% of body weight). Following walking exercise, subjects were required to wear 5 hours per day for 3 consecutive days GSC (SupportivTM) on one leg while the second was used as control. Muscle soreness and neuromuscular measures (M-wave, peak twitch, maximal voluntary torque or MVT) were taken pre and postwalk, then 2, 24, 48 and 72 hours post-walking exercise for the two legs. There was a 28% reduction in DOMS 72 h after exercise when wearing GCS (P<0.05) than in the control leg. Immediately after exercise there was a 15% decrease in MVT of the plantar flexors in both legs partly attributable to an alteration in contractile properties (-22% in electrically evoked mechanical twitch). In leg wearing GCS, MVT Starts to recover while the contractile properties had significantly recovered within 24 h but not in the control leg. In the current study, GCS might have had the effect of compressing the muscle tissue to such an extent that less structural damage occurred relative to a control condition. GCS accelerated the recovery of the muscle force capacity at 24 hours beyond that achieved by the control condition.